Two new steroidal saponins from Maianthemum henryi and their cytotoxic activity against human HepG2 tumor cells. Issue 24 (17th December 2019) - Lin, Jie; Wang, Guoquan; Bai, Lu; Yu, Linzhong
Abstract: Two new steroidal saponins (1 and2 ), along with four known ones (3 ∼ 6 ) were obtained from the roots and rhizomes of Maianthemum henryi, their structures were determined to be spirost-5, 25(27)-diene-l β, 3 β -diol 1- O - α -L-rhamnopyranosyl-(1 → 2)-4- O -acetyl- β -D-fucopyranoside (1 ), (23 S, 24 S )-spirost-5, 25(27)-diene-l β, 3 β, 23, 24-tetrol 1- O - α -L-rhamnopyranosyl-(1 → 2)-4- O -acetyl- β -D-fucopyranoside (2 ), spirost-5, 25(27)-diene-l β, 3 β -diol 1- O - α -L-rhamnopyranosyl-(1 → 2)- β -D-fucopyranoside (3 ), spirost-5, 25(27)-diene-l β, 3 β -diol 1- O - α -L-rhamnopyranosyl-(1 → 2)- β -D-xylopyranoside (4 ), Henryioside A (5 )、Henryioside B (6 ), by physicochemical properties and spectroscopic methods. In addition, their cytotoxic activity against human HepG2 tumor cells was evaluated by MTT method and all of the compounds exhibited cytotoxicity with the cells. Abstract :